Clinical manifestations and outcomes of Kawasaki Disease: A retrospective hospital-based data from Eastern India - Jyoti Ranjan Behera; Amit Ranjan Rup; Arun Kumar Dash; Mukesh Kumar Jain; Sanjay Kumar Sahu; Natabar Swain; Rasananda Polei (Indian Journal of Rheumatology)
Background: Kawasaki disease (KD) is a medium-vessel vasculitis having coronary predilection, usually affecting under-5 children presenting as acute febrile illness. Despite being a disease with long-term grievous outcome, only few published literature are available from India, even lesser from its eastern region. Methods: From January 2016 to December 2020, 30 case records of children with a discharge diagnosis of KD were enrolled in this study. Demographic profile, clinical manifestations, laboratory data, echocardiographic findings, and treatment done were extracted from the case records. Laboratory investigations were done at admission and repeated after 24 h of intravenous immunoglobulin administration as per the American Heart Association Guidelines 2004. Echocardiography was carried out at diagnosis, at 2 weeks, and at 6 weeks. Results: Out of 30 children diagnosed with KD, majority belong to 1–5 years of age group (72%) with male predominance. Complete KD was seen in 77% of children. The most common presentation was fever >5 days (100%) followed by oral changes in 26 (87%), conjunctivitis in 25 (83%), extremity changes in 23 (77%), and rash in 21 (70%) children. Desquamation of perineum and reactivation of bacillus Calmette–Guérin scar were seen in 10%. No children with complete KD and three children with incomplete KD developed coronary artery Abnormalities (CAA). Conclusion: Infants with incomplete KD have a higher incidence of CAA. Aggressive management results in better outcome.